2018
DOI: 10.1155/2018/4076548
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of 25-Hydroxyvitamin D Levels in Central Anatolia, Turkey

Abstract: Background/Aim The aim of this study is to evaluate serum 25-hydroxyvitamin D levels measured within one year at an Education and Research Hospital in Turkey to identify vitamin D insufficiency/deficiency (which is very commonly seen in the society) and to provide a current approach to treatment management. Materials and Methods This retrospective descriptive study was carried out by examining the data relating to 35,667 individuals. Results Of the individuals participating in the study, 94.47% had a serum 25-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 22 publications
0
21
0
4
Order By: Relevance
“…In Turkey, as in other countries around the world, vitamin D deficiency is endemic. Authors in a recent study claimed that 94.47% of women living in Turkey had serum 25(OH)D levels of less than 30 ng/ml, 76.25% had serum 25(OH)D levels of less than 20 ng/ml, and 32.20% had serum 25(OH)D levels of less than 10 ng/ml 11 .…”
Section: Introductionmentioning
confidence: 99%
“…In Turkey, as in other countries around the world, vitamin D deficiency is endemic. Authors in a recent study claimed that 94.47% of women living in Turkey had serum 25(OH)D levels of less than 30 ng/ml, 76.25% had serum 25(OH)D levels of less than 20 ng/ml, and 32.20% had serum 25(OH)D levels of less than 10 ng/ml 11 .…”
Section: Introductionmentioning
confidence: 99%
“…The findings of the present study are consistent with those of previous studies. Vitamin D deficiency is common in general population beacuse of living style (14). The rate of D vitamin deficiency/insufficiency with BTM was similar to general population.…”
Section: Discussionmentioning
confidence: 58%
“…The average Vitamin D level of the participants in this study was found to be 32.4±15.3 (ng/mL). In their retrospective study, Solak et al (2018) found the average serum 25-hydroxyvitamin D level as 15.2 ± 8.8 ng/ml. Other studies investigating the Vitamin D levels also reported that the 25-hydroxyvitamin D level was lower than 20ng/mL (Katrinaki et al, 2016;Mansoor et al, 2010;Yu et al, 2015).…”
Section: Discussionmentioning
confidence: 95%